Lobanovite, K2Na(Fe2+4Mg2Na)Ti2(Si4O12)2O2(OH)4, a new mineral of the astrophyllite supergroup and its relation to magnesioastrophyllite. (1st February 2017) - Sokolova, Elena; Cámara, Fernando; Hawthorne, Frank; Semenov, Evgeny; Ciriotti, Marco
Lobanovite, K2Na(Fe2+4Mg2Na)Ti2(Si4O12)2O2(OH)4, is a new mineral of the astrophyllite supergroup from Mt. Yukspor, the Khibiny alkaline massif, Kola Peninsula Russia. It has been known previously under the following names: monoclinic astrophyllite, magnesium astrophyllite, magnesiumastrophyllite and magne-sioastrophyllite but has never been formally proposed and approved as a valid mineral species by the Commission on new Minerals, Nomenclature and Classification of the International Mineralogical Association. It has now been revalidated and named lobanovite after Dr. Konstantin V. Lobanov, a prominent Russian ore geologist who worked in the Kola Peninsula for more than forty years (Nomenclature voting proposal 15-B). Lobanovite has been described from pegmatitic cavities on Mt. Yukspor where it occurs as elongated bladed crystals, up to 0.04 mm wide and 0.2 mm long, with a straw yellow to orange colour. Associated minerals are shcherbakovite, lamprophyllite, delindeite, wadeite, umbite and kostylevite. Lobanovite is biaxial (–) with refractive indices (λ = 589 nm) α = 1.658, βcalc. = 1.687, γ = 1.710; 2Vmeas. = 81.5– 83°. Lobanovite is monoclinic, space group C2/m, a = 5.3327(2), b = 23.1535(9), c = 10.3775(4) Å, β = 99.615(1)°, V = 1263.3 (1) Å3, Z = 2. The six strongest reflections in the powder X-ray diffraction data [d (Å), I, (hkl)] are: 3.38, 100, (003); 2.548, 90, (063); 10.1, 80, (001); 3.80, 60, (042, 131); 3.079, 50, (132, 062); 2.763, 90, (171). The chemical composition of lobanovite was determined by electron-microprobe analysis and the empirical formula (K1.97Ba0.01)∑1.98(Na0.65Ca0.14)∑0.79 (Fe2+3.18Mg2.02Na1.00Mn0.72)∑6.92(Ti1.99Nb0.06)∑2.05[(Si8.01Al0.06)∑8.07O24]O2(OH)4.03F0.19 was calculated on the basis of 30.2 (O + OH + F) anions, with H2O calculated from structure refinement, Dcalc. = 3.161 g cm–3. In the structure of lobanovite, the main structural unit is the HOH block, which consists of one close-packed O (Octahedral) and two H (Heteropolyhedral) sheets. The M(1–4) octahedra form the O sheet and the T4O12 astrophyllite ribbons and [5]-coordinated Ti-dominant D polyhedra link through common vertices to form the H sheet. The HOH blocks repeat along [001], and K and Na atoms occur at the interstitial A and B sites. The simplified and end-member formulae of lobanovite are K2Na [(Fe2+, Mn)4Mg2Na]Ti2(Si4O12)2O2(OH)4 and K2Na(Fe2+4Mg2Na)Ti2(Si4O12)2O2(OH)4, respectively.